Penerapan Model Picture and Picture Berbantuan Media Audio-Visual Untuk Meningkatkan Hasil Belajar Bahasa Indonesia Siswa Kelas II - Tohriah, Tohriah; Rati, Ni Wayan (Universitas Pendidikan Ganesha, 2018)
The purpose of this research was to know the improvement of students’ learning outcomes of Indonesian subject in class IIB SD Undiksha Laboratory academic year 2017/2018 after applying model picture and picture assisted with audio visual media. The present research was a classroom action research held in 2 cycles. Every cycle consisted of the planning stages, the implementation, observation and evaluation and reflection. Methods used in collecting the data in this research was administering observation and test. In the first cycle, the average percentage of learning outcomes obtained was 82.67% and the average score of learning activities was 73.50 in which categorized as active, and teacher’s activity was categorized good with a score of 73.50. In second cycle data of learning result and activity of student and teacher had increased with 90,11% of average percentage of learning result and categorized very high, and students’ activity average score was 81,00 in which categorized active, teacher’s activity was categorized good with score equal to 81.00. Thus, it could be concluded that the application of picture and picture model assisted with audio-visual media could improve the students’ learning outcomes of Indonesian subject in class IIB SD Undiksha Laboratory academic year 2017/2018.